PO020 First case of hev presenting with rhombencephalitis and gbs. (1st December 2017) - Salim, Omar; Davidson, Amy; Heath, Craig; Li, Kathy; Leach, John Paul
Abstract : A 59 year old right handed lorry driver presented with acute pyrexial illness. He was GCS 15, had reduced VA in left eye to finger counting associated with partial left ptosis and mild left hemiparesis with an extensor plantar on left. Over 48 hours, he accrued multiple CN palsies, had a fluctuating conscious level, and progressed to a flaccid paralysis of all muscle groups requiring admission to ICU. CSF showed 20 WBC, 100% lymphocytes. Protein was raised at 1.65 g/L with negative viral and bacterial PCR. Samples for Lyme, blood-borne viruses, syphilis and auto-antibodies were negative. MRI brain scan showed T2 abnormalities and restriction of diffusion within the brainstem. Nerve conduction studies revealed an AMSAN pattern. The patient was treated for both infective and inflammatory causes of brainstem encephalitis and GBS. Hepatitis E serology was tested on a blood sample and was positive for HEV IgG and IgM in keeping with an acute infection. Retrospective PCR testing of CSF from admission and stored bloods prior to IVIG infusion confirmed this. All HEV genotypes have been associated with GBS and Rhombencephalitis but not both simultaneously! We postulate this is what has driven this patient's neurological syndrome with improvement occurring after natural clearance.